The Implementation of Project-based Learning to Encourage Learner Autonomy (RETAIN, 2020)
Project-based learning is a method that could maximize students’ role by implementing student-centered approach using a project. By maximizing students’ role, it will promote their learner autonomy. Learner autonomy is an important ability to support teaching-learning process. Therefore, this research is aimed to investigate how project-based learning could encourage learner autonomy and how the students’ perceptions toward the implementation of project-based learning to encourage learner autonomy. This study applies a qualitative research design at tenth graders in one of Senior high school in Kediri. An observation checklist, questionnaire, and semi-structured interview used to collect the data. The data were analyzed qualitatively through familiarizing and organizing, coding and reducing, also interpreting and representing step. The results show that in each step in implementing project-based learning, learner autonomy that covered by self-instruction, self-direction, self-access, and individualized instruction were implemented. Furthermore, the second results present that students assume learner autonomy can be promoted through project-based learning by giving the students larger opportunities to engage and freedom in learning.